2013
DOI: 10.5194/nhess-13-1691-2013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flood risk characteristics on flood insurance demand: a comparison between Germany and the Netherlands

Abstract: The existence of sufficient demand for insurance coverage against infrequent losses is important for the adequate function of insurance markets for natural disaster risks. This study investigates how characteristics of flood risk influence household flood insurance demand based on household surveys undertaken in Germany and the Netherlands. Our analyses confirm the hypothesis that willingness to pay (WTP) for insurance against medium-probability medium-impact flood risk in Germany is higher than WTP for insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 56 publications
(30 reference statements)
1
65
0
Order By: Relevance
“…Cases of fluvial flooding are not included in the data, as these are not commonly covered by property and content insurance policies in the Netherlands (Seifert et al, 2013). Insurers typically compensate for the costs of cleaning, drying and replacing materials and objects, and the costs of temporarily rehousing people.…”
Section: Damage Variablesmentioning
confidence: 99%
“…Cases of fluvial flooding are not included in the data, as these are not commonly covered by property and content insurance policies in the Netherlands (Seifert et al, 2013). Insurers typically compensate for the costs of cleaning, drying and replacing materials and objects, and the costs of temporarily rehousing people.…”
Section: Damage Variablesmentioning
confidence: 99%
“…And fifthly, policy-holders or potential policy-holders do not always behave rationally; people tend to underestimate low-probability risks and their need for insurance Kunreuther, 20 1996). Their decision to purchase insurance relies on their risk perception, previous experience, previous provision of governmental loss compensation, and other factors (Seifert et al, 2013). There is a large body of literature studying behavioral determinants of insurance purchase (see e.g.…”
Section: Agreements With State Actorsmentioning
confidence: 99%
“…For insurance markets to function adequately it is imperative that there should be the existence of sufficient demand. Seifert et al (2013) in their study of disaster insurance demand between Germany and Netherland's found that the willingness to pay(WTP) for insurance is lower in Netherlands' for low probability high impact flood than a medium probability medium impact flood in Germany. They concluded that there was a need to make insurance mandatory or design information campaigns.…”
Section: Tackling the Issue Of Underinsurancementioning
confidence: 99%